Long-term effects of early adversity on the mental health of college students: The mitigating effect of physical exercise - Wang, Xinzhu; Fu, Kaixian (Frontiers in Psychology, 2023)
Background We aim to investigate the long-term effects of early adversity on university students’ mental health and the mitigating role of physical exercise on this effect. Methods The survey sample consisted of 895 college students. Descriptive statistics, linear regression, and moderating effect analysis were used to analyze the results. Results (1) Early adversity negatively predict mental health level (β = −0.109, t = −4.981, p < 0.01); (2) Physical exercise can effectively mitigate the long-term harm of early adversity to mental health (β = 0.039, t = 2.001, p < 0.05); compared to low-level physical exercise (bsimple = −0. 067, t = −7.88, p < 0.01), high-level physical exercise can mitigate the long-term harm of early adversity to mental health (bsimple = −0, 025, t = −2. 37, p < 0.01). Conclusion Early adversity affects the mental health of university students, but physical exercise can effectively mitigate this effect.